Tolerancia in vitro de Fusarium solani y Fusarium semitectum (anamorfos, Ascomycota) a la exposición a desinfectantes de superficie utilizados en acuicultura In vitro tolerance of Fusarium semitectum and Fusarium solani (anamorphic, Ascomycota) ... - Suani G. Pacheco Marino; Marta N. Cabello; Alfredo Salibián (Boletín de la Sociedad Argentina de Botánica, 2013)
Summary: In vitro tolerance of Fusarium semitectum and Fusarium solani (anamorphic, Ascomycota) exposed to surface disinfectant commonly used in aquaculture. An in vitro evaluation of the antifungal effect of acetic acid (AcH), buffered acetic acid (AcH+AcNa), potassium iodide (KI) and Iodopovidone (IP); on the growth rate (GR) of Fusarium solani (Mart.) Sacc. 1881 and Fusarium semitectum Berk. & Ravenel, 1875 was performed. Both fungal species were isolated from eggs of the Argentinian silverside Odontesthes bonariensis (Cuvier & Valenciennes, 1835). The studied substances are commonly used in fish farming as surface disinfectants. The tested concentrations of this substances exhibited antifungal activity for both strains at concentrations higher than their 96h median lethal concentrations (LC50-96h) for the treated eggs; concentrations below the (LC50-96h) exhibited little or no effect.